Consumers Preference For Home Service Clinical Laboratory Tests During Covid-19 Pandemic In Indonesia - Astra Larasati; Eko Prayitno; Garindra Ibrahim; Jeffrey Jeffrey; Melinda Nastasya (Institut Manajemen Wiyata Indonesia, 2022)
COVID-19 pandemic has created a crisis in many industry sectors around the world. This situation drives changes in consumer behavior in doing their activities. Indonesian consumers’ high tendency to do activities at home is seen as an opportunity by clinical laboratory providers. As a part of the healthcare system, clinical laboratory providers rethink their ways in approaching more consumers in the midst of pandemic disruptions. This study aims to know what factors influence consumers’ preference to choose diagnostic testing conducted at home. The research findings indicate that Consumer Preferences towards Home Service Clinical Laboratory Tests are significantly affected by Perceived Behavioral Control, Subjective Norms, Perceived Cost-Benefit, and Information consecutively.